Increased response of vegetation to soil moisture in the northern hemisphere drylands - Wang, Xi; Zhao, Fubo; Wu, Yiping (Frontiers in Earth Science, 2023)
Vegetation plays a significant role in terrestrial ecosystems due to its strong carbon absorption capability and multiple feedback effects on the climate system. The soil moisture availability determines vegetation growth, especially in the drylands. Although there has been increasing interest in issues such as the vegetation’s response to a specific climate variable, it remains unclear how soil moisture can quantitatively influence the vegetation in the drylands. In this study, we investigated the increased response of the vegetation to soil moisture and identified its key mechanism in the northern hemisphere drylands (NHD) from 1982 to 2010. The Methods included the use of the Lindeman-Merenda-Gold method. The results showed that the sensitivity of the vegetation dynamics to soil moisture significantly increased over the past 29 years (slope = 0.008, p < 0.0001), and the trend during 1996–2007 (slope = 0.025 m3/m3/yr, p < 0.0001) increased more rapidly than the trend during 1984–1995 (slope = -0.005 m3/m3/yr, p = 0.0143), which indicates increased water restrictions in recent years. Further analysis showed that atmospheric CO2 was the major contributor (27.2%) to the sensitivity changes, followed by climate change (27%), and nitrogen deposition (19%). The changes in the ecosystem structure (represented by the non-tree cover areas) and climate vacillation contributed similarly to the sensitivity change (14% and 12%). These findings can help with understanding the spatiotemporal impact of water restrictions on vegetation in the NHD and the related influencing mechanisms of vegetation growth and soil moisture in the greening and warming of the NHD.